1959
DOI: 10.1111/j.1744-7348.1959.tb03494.x
|View full text |Cite
|
Sign up to set email alerts
|

EXPERIMENTS ON THE MODE OF ACTION OF INSECTICIDAL SEED‐DRESSINGS, ESPECIALLY AGAINST LEPTOHYLEMYIA COARCTATA FALL., MUSCIDAE, THE WHEAT BULB FLY

Abstract: Certain chlorinated hydrocarbon insecticides applied as seed‐dressings to wheat can kill wheat bulb fly larvae either by contact or by systemic action. Newly hatched larvae may be killed by contact action when they pass close to the treated seed on their way to attack the shoot. Such kill depends on the behaviour of the larvae and on the depth the seed is sown. Larvae move upwards after hatching and probably reach the surface soil where they search for the host plant, entering the shoot at a depth of between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1959
1959
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 19 publications
(17 reference statements)
1
11
0
Order By: Relevance
“…If this assumption is correct, then the larvae found dead in the shoots must have picked up a lethal dose of insecticide when moving towards the plant through the "zone of protection" afforded by these chemicals. This emphasizes the importance of shallow drilling (Way, 1959).…”
Section: Discussionmentioning
confidence: 83%
“…If this assumption is correct, then the larvae found dead in the shoots must have picked up a lethal dose of insecticide when moving towards the plant through the "zone of protection" afforded by these chemicals. This emphasizes the importance of shallow drilling (Way, 1959).…”
Section: Discussionmentioning
confidence: 83%
“…If larvae move in the upper layers of soil before burrowing down to enter the bulb of the plant, as suggested by Way (1959) and by Long (1958), larvae could enter plants without coming into contact with insecticide, and Way (1959) showed that with deep sowing y-BHC and dieldrin seed-dressings were less effective against wheat bulb fly either as contact or as systemic poisons.…”
Section: Discussionmentioning
confidence: 98%
“…Dieldrin and y-BHC seed-dressings have been used for more than 10 years to control wheat bulb fly. Results of many trials have shown that y-BHC acts mainly by preventing larvae entering the plants and kills few larvae that succeed in entering, whereas dieldrin acts mainly by killing larvae after they enter (Gough & Woods, 1954;Bardner, 1958;Way, 1959;Maskell & Gair, 1961 ;Gough, Woods, Maskell & Towler, 1961). Both materials are less effective in organic soils than in mineral soils (Gough et al, 1961.…”
Section: Introductionmentioning
confidence: 99%
“…The examination for pupae made on 15 August 1958 showed that the dieldrin treatments did not kill frit larvae during their development in the plant. Similar dieldrin treatments would almost certainly have killed nearly all wheat bulb fly larvae by systemic action (Way, 1959). The species of host plant therefore seems not to be responsible for the dieldrin seed-dressings failing to kill frit fly larvae by systemic action.…”
Section: Effect Of Close Contact Between Seed and Insecticidementioning
confidence: 96%
“…A dieldrin seed-dressing will effectively control attacks on seedling crops by some Diptera Muscidae. For example, it prevents damage to ionions by the onion fly, Delia antiqua Meig., probably by contact action on the young larva before it enters the plant (Way, 1959). The action of dieldrin against wheat bulb fly Lepto-hyZemyia coarctata Fall.…”
Section: Introductionmentioning
confidence: 99%